PTH-081 The use of dry blood spot testing for hepatitis C within needle exchange services. (23rd September 2015) - Stephens, B P; Keeffe, S O; Tait, J M; McIntyre, P; Dillon, J F
Abstract : Introduction: Diagnosing hepatitis C virus (HCV) in current injecting drug users has often proved challenging. This is due to the individuals reluctance to have medical staff obtain venous blood from their preferred injecting sites in addition to generally poor venous access. Dry blood spot testing (DBST) has proven to be a robust method of determining HCV status. The aim of this study was to evaluate the ease of use of DBST in clinical practice. Methods: This was a 3-month pilot study. Staff within a needle exchange service were given appropriate training in the use of DBST. Testing for HCV was offered to all individuals who accessed needle exchange services during this period. A follow-up appointment was given for 2 weeks after testing and a referral to specialist services was offered to those individuals who tested positive. Results: A total of 140 individuals were tested during the study period, 100% of samples obtained were processed successfully. 63.6% (89/140) of the individuals tested were male, the age range was between 18 and 51 years. 92.9% (130/140) attended a follow-up appointment for their results. Of the 7.1% who did not receive results, 2.9% (4/140) were HCV positive and 4.3% (6/140) were negative. 30.7% (43/140) were positive for HCV antibodies. Of the 39 individuals who received their positive results, all were offered referral to specialist services and only 10% (4/39) did not wish further input at this time. Of the 35 referred into specialist service 88% (31/35) have attended an appointment to be reviewed by the specialist team to provide further information and/or check HCV PCR. Conclusion: The study has shown DBST is easy to use and can be carried out without difficulty by staff within drug services. The offer of HCV testing was well received by the particular client group and over 90% of individuals returned for their results. Knowing HCV status also allowed staff to reiterate the appropriate harm reduction measures. 90% accepted referral to specialist services and 88% attended a follow-up appointment therefore suggesting that providing BBV testing is valuable in a group who are often envisaged as being too chaotic to engage with health services.